Analysis of Social-Emotional Influences on the Language Development of Primary School Children - Khosiyono, Banun Havifah Cahyo; Al Adib, Amin; Sulaimon, Jamiu Temitope (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Rapid child development at primary school age involves language, emotional, and social development. Factors that influence us are the family environment and primary school. This study aims to analyze social-emotional influences on the language development of primary school children. This type of research is a qualitative case study. The participants are primary school children and teachers. Data collection for this study used observation and teacher interviews. The results of this study indicate that the language, emotional, and social development of primary school-aged children happens quickly. Every youngster develops differently from the next. This growth can be influenced by a variety of circumstances, such as the home and school environment. Teachers can use the study of this development as a guide to implement learning in classrooms and identify issues that arise there. The implications of this study are that it might help educators solve issues with learning and child development.